2021
DOI: 10.1029/2021ms002581
|View full text |Cite
|
Sign up to set email alerts
|

FORCAsT‐gs: Importance of Stomatal Conductance Parameterization to Estimated Ozone Deposition Velocity

Abstract: Photosynthesis and transpiration of the world's forests drive the carbon, hydrological and nutrient cycles, governing climate, ecosystem health and productivity, and biodiversity. Forests also serve as a sink for trace gases which are deposited onto plant surfaces and taken up through the stomata. Dry deposition of ozone is of particular importance as it represents a major sink of this tropospheric pollutant. It is also of particular concern because ozone can damage photosynthetic apparatus limiting growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Several papers in the collection go into specific modeling advances to improve scale‐relevant processes. These include work on improving plant water cycling with hydrodynamic approaches (Bohrer & Missik, 2022) and advancing stomatal conductance formulations (Otu‐Larbi et al., 2021). New approaches to move beyond plant functional types to detailed species and land use delineations were found to be important for air quality modeling (Luttkus et al., 2022), biogenic volatile organic compound crop emission models (Havermann et al., 2022), and for site‐level data assimilation in ecosystem models (Jung & Hararuk, 2022).…”
Section: Scaling a Mountainmentioning
confidence: 99%
“…Several papers in the collection go into specific modeling advances to improve scale‐relevant processes. These include work on improving plant water cycling with hydrodynamic approaches (Bohrer & Missik, 2022) and advancing stomatal conductance formulations (Otu‐Larbi et al., 2021). New approaches to move beyond plant functional types to detailed species and land use delineations were found to be important for air quality modeling (Luttkus et al., 2022), biogenic volatile organic compound crop emission models (Havermann et al., 2022), and for site‐level data assimilation in ecosystem models (Jung & Hararuk, 2022).…”
Section: Scaling a Mountainmentioning
confidence: 99%
“…Stomatal uptake typically accounts for 40%-90% of forest ozone uptake during the growing season (Fowler et al, 2009), but the contribution by individual sink terms is poorly constrained by parameterizations of land-atmosphere exchange in global and regional atmospheric chemistry models (Clifton et al, 2020). Multi-parameterization intercomparisons indicate that these uncertainties lead to a large spread in simulated ozone deposition, attributed to the description of stomatal and various non-stomatal ozone removal processes (Otu-Larbi et al, 2021;Visser et al, 2021;Wu et al, 2018). Likewise, Clifton et al (2017) found that inter-annual variability in the ozone deposition velocity in a global atmospheric chemistry model was underestimated by a factor two compared to an 11-year ozone flux data set, and attributed this to year-to-year variability in non-stomatal removal.…”
mentioning
confidence: 99%